Time series test of nonlinear convergence and transitional dynamics - Chong, Terence Tai-Leung; Hinich, Melvin J.; Liew, Venus Khim-Sen; Lim, Kian-Ping (Elsevier Ltd., 2008)
This paper revisits the income convergence hypothesis by using the nonlinear unit root test of Kapetanios et al. [Kapetanios, G., Shin, Y. and A. Snell, 2003. Testing for a unit root in the nonlinear STAR framework. Journal of Econometrics 112, 359–379.]. Out of the 12 OECD income gaps in which nonlinearity has been detected, two cases of long-run converging and four cases of catching up are found.